Effect of oxygen content on magnetization and magnetoresistance properties of CMR manganites - Trukhanov, S.V.; Troyanchuk, I.O.; Korshunov, F.P.; Sirenko, V.A.; Szymczak, H.; Baerner, K. (Физика низких температур, 2001)
The influence of oxygen content on the magnetization and electrical resistivity of Ln₀.₅A₀.₅MnO₃ (Ln=La,Pr,Nd; A=Ca,Ba) manganites with the perovskite structure is investigated. It is shown that the La₀.₅Ca₀.₅MnO₃₋γ compound undergoes a sequence of transitions from an antiferromagnetic (γ=0) to a spin-glass (γ=0.17) state and then to an inhomogeneous ferromagnetic (γ=0.3) state. A transition from an antiferromagnetic charge-ordered state to a ferromagnetic charge-disordered state in Nd₀.₅Ca₀.₅ MnO₃₋γ is observed as the oxygen content is reduced to where γ=0.07. The Nd₀.₅Ba₀.₅ MnO₃₋γcompound shows an increase of the Curie point from 110 K (γ=0) up to 310 K (γ=0.3). In addition, a large magnetoresistance is revealed which develops below their Curie temperature despite the absence of Mn³⁺√Mn⁴⁺ pairs. A Zener double-exchange interaction is usually used in literature to explain the magnetic and electrical properties of hole-doped perovskite manganites. The data obtained support the mechanism of superexchange interactions between magnetic moments of the manganese ions via oxygen.